Dinamika Pemasaran Politik Melalui Media Sosial Tiktok (Studi Pada Akun @Zul.hasan, @Agusyudhoyono10, Dan @Airlanggahartarto) - Akbar Julio, Muhammad; Julio, Muhammad Akbar; Zalpa, Yulion; Rentika Wati, Reni (Jurnal Studi Ilmu Politik, 2025)
This research aims to find out the Dynamics of Political Marketing through Tiktok Social Media and to find out the strategies and methods of political marketing on @zul.hasan, @agusyudhoyonoahy, and @airlanggahartarto accounts. The theory of this research uses 4 political marketing mixes according to Firmanzah and the theory of segmentation, target, position (STP). The subjects in this study are Zulkifli Hasan, Agus Yudhoyono, and Airlangga Hartarto. This research method uses descriptive qualitative research where descriptive qualitative research is research that describes and analyzes the data obtained and will then be described in the form of an explanation that is actually not in the form of numbers but uses a drawer that occurs in the field through documentation. The data sources used are primary data and secondary data. Research data analysis techniques are in the form of interviews, documentation, observations and other data sources so that they are easy to understand and then can be informed to the public. Based on the results of the study, it can be concluded that the three figures of Zulkifli Hasan, Agus Yudhoyono, and Airlangga Hartarto implemented a good and effective political marketing strategy by using the Firmanzah Product, Promotion, Price, and Place political marketing strategy as well as the STP strategy well, precisely, and directionally. The supporting factor for the political marketing strategy process of these three political figures is segmentation community, external aspects of the success team, network of friends, and internal aspects that are the mission of the three figures.